Special low-conductivity cooling liquid for electric vehicle and preparation method of special low-conductivity cooling liquid

By using specific formulas in electric vehicle coolant, including ethylene glycol, sodium nitrate and other ingredients, the problems of electric vehicle spontaneous combustion and metal corrosion caused by high conductivity of existing coolant are solved, and the preparation of coolant with low conductivity and high corrosion resistance is achieved, ensuring the safety and stability of the electric vehicle system.

CN119799288APending Publication Date: 2025-04-11SHANGHAI INST OF TECH +1

Patent Information

Application Number
CN202411729287.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The current coolant has a high conductivity, which leads to the electric vehicle power batteries prone to spontaneous combustion in the event of liquid leakage, and the additives in the coolant will corrode the metal material, affecting the service life.

Method used

A low-conductivity electric vehicle special coolant is used, and its formulation includes ethylene glycol, sodium nitrate, caprylic acid, butyl phosphate, styrene triazole, polyether modified silicone defoaming agent, triethanolamine, imidazole, pigment blue and limonin. Through the combination of these components, the conductivity of the coolant is reduced and effective metal anti-corrosion protection is provided.

Benefits of technology

The preparation of low-conductivity coolant is achieved, effectively reducing the risk of spontaneous combustion of electric vehicle power batteries in the case of leakage, and extending the service life of the coolant and the stable operation of the electric vehicle system through excellent corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799288A_ABST
    Figure CN119799288A_ABST
Patent Text Reader

Abstract

The invention discloses a special low-conductivity cooling liquid for an electric vehicle and a preparation method thereof, and the special low-conductivity cooling liquid comprises ethylene glycol, sodium nitrate, octanoic acid, butyl phosphate, benzotriazole, a polyether modified organic silicon defoamer, triethanolamine, imidazole, pigment blue and limonin. The high-temperature-resistant and corrosion-resistant coating is prepared from the following components in percentage by mass: 95 to 100 percent of ethylene glycol, 0 to 0.05 percent of sodium nitrate, 0.2 to 0.4 percent of octanoic acid, 0 to 0.01 percent of butyl phosphate, 0.1 to 0.4 percent of benzotriazole, 0.05 to 0.1 percent of polyether modified organic silicon defoaming agent, 0.5 to 2 percent of triethanolamine, 0 to 0.3 percent of imidazole, 0.02 to 0.06 percent of pigment blue and 0.05 to 0.1 percent of limonin. On the basis of meeting the new national standard of the electric vehicle cooling liquid, the electric vehicle cooling liquid has low conductivity, fire caused by leakage of the cooling liquid can be effectively prevented, and the cooling liquid can effectively provide protection for a new energy electric vehicle system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coolants, and in particular relates to a low-conductivity coolant specially used for electric vehicles and a preparation method thereof. Background Art

[0002] In recent years, with the rise of new energy electric vehicles, the safety performance and service life of electric vehicle power batteries have become one of the most concerned issues. Among them, the spontaneous combustion of electric vehicles is frequent, slightly higher than that of traditional fuel vehicles. It mainly occurs during the driving and charging stages of the vehicle, especially at high temperatures. In order to ensure the continuous and effective operation of power batteries, thermal management is an important way to control the temperature of the system. Liquid cooling has a large specific volume and a high heat transfer coefficient. It is currently the most mainstream cooling technology for electric vehicles. At the same time, it is also accelerating its promotion in the fields of energy storage and data centers.

[0003] Studies have shown that the main reasons for the spontaneous combustion of electric vehicles are short circuits in the power battery and the deformation and squeezing of the battery shell, which causes leakage of the single battery. Therefore, when leakage occurs, the higher the conductivity of the coolant, the greater the heat released in the short circuit, leading to spontaneous combustion. If the conductivity of the coolant can be controlled to be low, the heat generation power can be effectively reduced. The alcohol substances in the coolant will undergo oxidation and acidification during use, causing the pH value to change. At the same time, there will be additives such as rust inhibitors, corrosion inhibitors, and defoaming agents in the coolant, which will cause a certain degree of corrosion to the metal materials in the electric vehicle, and will also increase the ion content in the coolant, resulting in increased conductivity and affecting the service life.

[0004] Patent CN118326401A discloses a method for preparing a composite corrosion inhibitor and an environmentally friendly coolant, wherein the corrosion inhibitor is mainly heterocyclic, fatty acid, aromatic, and does not contain toxic and harmful substances such as nitrite and phosphate. Through glassware corrosion test, the coolant has excellent protection performance in metal corrosion protection, and the weight loss of various metals does not exceed 3.0 mg, but its conductivity is high and cannot play a good protective role. Patent CN117946636 discloses a method for preparing a low-conductivity coolant, which mainly adopts electrolyte-free solute (one or combination of diols and triols) and non-ionic surfactant to reduce conductivity, and uses distilled water to clean the container. The conductivity of the aqueous solution after cleaning and the conductivity of distilled water used in the preparation are maintained at 1μs / cm, but the additives in the coolant will be relatively reduced while reducing the conductivity, so that the corrosion degree of the metal is increased.

[0005] Therefore, the coolant must have a lower electrical conductivity to effectively prevent fires caused by coolant leakage, and it must also be able to provide effective protection for new energy electric vehicle systems, which is a problem that needs to be urgently solved in existing technologies. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a low-conductivity cooling liquid specifically for electric vehicles.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a low-conductivity electric vehicle-specific coolant, characterized in that: the low-conductivity electric vehicle-specific coolant comprises ethylene glycol, sodium nitrate, octanoic acid, butyl phosphate, phenyltriazole, polyether-modified silicone defoamer, triethanolamine, imidazole, pigment blue, and limonin;

[0010] Among them, calculated by mass fraction, ethylene glycol is 95-100%, sodium nitrate is 0-0.05%, caprylic acid is 0.2-0.4%, butyl phosphate is 0-0.01%, benzotriazole is 0.1-0.4%, polyether modified silicone defoamer is 0.05-0.1%, triethanolamine is 0.5-2%, imidazole is 0-0.3%, pigment blue is 0.02-0.06%, and limonin is 0.05-0.1%.

[0011] As a preferred embodiment of the low-conductivity electric vehicle-specific coolant of the present invention, the low-conductivity electric vehicle-specific coolant comprises, by mass fraction, 98.352% of ethylene glycol, 0.03% of sodium nitrate, 0.3% of octanoic acid, 0.008% of butyl phosphate, 0.12% of benzotriazole, 0.08% of polyether-modified silicone defoamer, 1% of triethanolamine, 0.04% of pigment blue, and 0.07% of limonin.

[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a low-conductivity cooling liquid for electric vehicles, which is characterized by comprising:

[0013] The ingredients are prepared according to the mass percentages as described in any one of claims 1 to 2, ethylene glycol, sodium nitrate and deionized water are added to the reactor in sequence, and stirred sufficiently to mix them evenly; then octanoic acid and butyl phosphate are added and stirred continuously until they are evenly mixed; finally benzotriazole and defoaming agent are added and stirred evenly until no turbidity exists; then triethanolamine and imidazole are added to the reactor, stirred to make them evenly distributed; finally pigment blue and bittering agent are added and stirred until they are evenly mixed; the mixture is filtered using filter cloth to obtain the low-conductivity electric vehicle-specific coolant.

[0014] As a preferred embodiment of the preparation method of the present invention, ethylene glycol, sodium nitrate and deionized water are sequentially added into a reaction kettle and stirred sufficiently to mix them evenly, wherein the stirring time is 20 to 40 minutes.

[0015] As a preferred embodiment of the preparation method of the present invention, the stirring time for adding octanoic acid and butyl phosphate and continuously stirring until uniform mixing is 20 to 40 minutes.

[0016] As a preferred embodiment of the preparation method of the present invention, the stirring time of adding triethanolamine and imidazole into the reaction kettle is 30 to 50 minutes.

[0017] As a preferred embodiment of the preparation method of the present invention, the stirring time for adding the pigment blue and the bittering agent until they are evenly mixed is 5 to 10 minutes.

[0018] As a preferred embodiment of the preparation method of the present invention, the stirring time for adding benzotriazole and defoaming agent is 30 to 50 minutes.

[0019] As a preferred embodiment of the preparation method of the present invention, the conductivity of the ultrapure water solution used in the reaction kettle is lower than 0.3 μs / cm.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a low-conductivity electric vehicle-specific coolant for use in electric vehicles.

[0021] Beneficial effects of the present invention:

[0022] The triethanolamine in the present invention can not only provide excellent protection for cast iron parts, form a protective film on its surface, reduce the risk of corrosion damage, but also serve as a PH buffer to maintain the acid-base balance of the coolant and ensure stable performance. Sodium nitrate is an excellent corrosion inhibitor. It builds a protective film on the metal surface to slow down corrosion. When used in combination with sodium hydroxide, it can inhibit the embrittlement of boiler metals, provide effective protection for aluminum parts, reduce the incidence of failures, and extend the life of equipment. As a corrosion inhibitor, octanoic acid can be adsorbed on the metal surface to form a barrier layer, inhibit corrosion reactions, and protect the metal parts of the cooling system. As a preservative, butyl phosphate can inhibit the growth and reproduction of microorganisms, prevent the coolant from deteriorating and producing corrosive substances, thereby extending the service life of the coolant and reducing the failure and maintenance costs of the cooling system. Benzotriazole can effectively protect copper and copper alloys from corrosion. These additives play different roles in the coolant system, making the coolant performance more superior and providing reliable protection for the electric vehicle cooling system. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0024] Figure 1 This is a comparison diagram of the changes before and after the static glassware corrosion experiment test piece of the present invention.

[0025] Figure 2 This is a comparison chart of the changes before and after the hot surface corrosion test of the cast aluminum test block of the present invention.

[0026] Figure 3 This is a comparison chart of the changes before and after the cyclic bench corrosion test specimen of the present invention. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.

[0031] Table 1

[0032]

[0033]

[0034] Example 1

[0035] (1) Use ultrapure water prepared by a water purifier to wash the reactor and the beaker container used in the preparation process multiple times, so that the conductivity of the ultrapure water solution is less than 0.3 μs / cm;

[0036] (2) Weighing the raw material components, the specific mass fractions are as follows: ethylene glycol 98.352%, sodium nitrate 0.03%, octanoic acid 0.3%, butyl phosphate 0.008%, benzotriazole 0.12%, polyether modified silicone defoamer 0.08%, triethanolamine 1%, imidazole 0%, pigment blue 0.04%, limonin 0.07%;

[0037] (3) Ethylene glycol and sodium nitrate are added to the cleaned reactor in sequence and stirred thoroughly to mix them evenly; then, octanoic acid and butyl phosphate are added to the reactor and stirred continuously until they are evenly mixed; then, benzotriazole and defoaming agent are added to the reactor and stirred evenly until no turbidity exists; then, triethanolamine and imidazole are added to the reactor and stirred to make them evenly distributed; then, pigment blue and bittering agent are added to the reactor and stirred until they are evenly mixed;

[0038] (4) adding the above coolant to ultrapure water prepared by a water purifier so that the volume fraction of ethylene glycol is 50%;

[0039] (5) After stirring evenly, filter with filter cloth and take samples to test the physical and chemical properties and performance of the coolant.

[0040] Example 2

[0041] (1) Use ultrapure water prepared by a water purifier to wash the reactor and the beaker container used in the preparation process multiple times, so that the conductivity of the ultrapure water solution is less than 0.3 μs / cm;

[0042] (2) Weighing the raw material components, the specific mass fractions are as follows: ethylene glycol 98.322%, sodium nitrate 0.03%, octanoic acid 0.3%, butyl phosphate 0.008%, benzotriazole 0.15%, polyether modified silicone defoamer 0.08%, triethanolamine 1%, imidazole 0%, pigment blue 0.04%, limonin 0.07%;

[0043] (3) Ethylene glycol and sodium nitrate are added to the cleaned reactor in sequence and stirred thoroughly to mix them evenly; then, octanoic acid and butyl phosphate are added to the reactor and stirred continuously until they are evenly mixed; then, benzotriazole and defoaming agent are added to the reactor and stirred evenly until no turbidity exists; then, triethanolamine and imidazole are added to the reactor and stirred to make them evenly distributed; then, pigment blue and bittering agent are added to the reactor and stirred until they are evenly mixed;

[0044] (4) adding the above coolant to ultrapure water prepared by a water purifier so that the volume fraction of ethylene glycol is 50%;

[0045] (5) After stirring evenly, filter with filter cloth and take samples to test the physical and chemical properties and performance of the coolant.

[0046] Example 3

[0047] (1) Use ultrapure water prepared by a water purifier to wash the reactor and the beaker container used in the preparation process multiple times, so that the conductivity of the ultrapure water solution is less than 0.3 μs / cm;

[0048] (2) Weighing the raw material components, the specific mass fractions are as follows: ethylene glycol 97.647%, sodium nitrate 0%, octanoic acid 0.3%, butyl phosphate 0.003%, benzotriazole 0.24%, polyether modified silicone defoamer 0.08%, triethanolamine 1.5%, imidazole 0.12%, pigment blue 0.04%, limonin 0.07%;

[0049] (3) Ethylene glycol and sodium nitrate are added to the cleaned reactor in sequence and stirred thoroughly to mix them evenly; then, octanoic acid and butyl phosphate are added to the reactor and stirred continuously until they are evenly mixed; then, benzotriazole and defoaming agent are added to the reactor and stirred evenly until no turbidity exists; then, triethanolamine and imidazole are added to the reactor and stirred to make them evenly distributed; then, pigment blue and bittering agent are added to the reactor and stirred until they are evenly mixed;

[0050] (4) adding the above coolant to ultrapure water prepared by a water purifier so that the volume fraction of ethylene glycol is 50%;

[0051] (5) After stirring evenly, filter with filter cloth and take samples to test the physical and chemical properties and performance of the coolant.

[0052] Example 4

[0053] (1) Use ultrapure water prepared by a water purifier to wash the reactor and the beaker container used in the preparation process multiple times, so that the conductivity of the ultrapure water solution is less than 0.3 μs / cm;

[0054] (2) Weighing each raw material component, the specific mass fraction is as follows: ethylene glycol 97.547%, sodium nitrate 0%, octanoic acid 0.3%, butyl phosphate 0.003%, benzotriazole 0.24%, polyether modified silicone defoamer 0.08%, triethanolamine 1.6%, imidazole 0.12%, pigment blue 0.04%, limonin 0.07%;

[0055] (3) Ethylene glycol and sodium nitrate are added to the cleaned reactor in sequence and stirred thoroughly to mix them evenly; then, octanoic acid and butyl phosphate are added to the reactor and stirred continuously until they are evenly mixed; then, benzotriazole and defoaming agent are added to the reactor and stirred evenly until no turbidity exists; then, triethanolamine and imidazole are added to the reactor and stirred to make them evenly distributed; then, pigment blue and bittering agent are added to the reactor and stirred until they are evenly mixed;

[0056] (4) adding the above coolant to ultrapure water prepared by a water purifier so that the volume fraction of ethylene glycol is 50%;

[0057] (5) After stirring evenly, filter with filter cloth and take samples to test the physical and chemical properties and performance of the coolant.

[0058] The physical and chemical properties of the coolants of Examples 1 to 4, including freezing point, density, conductivity, and pH value, were tested. The test related instruments and standard methods are shown in Table 2, and the test results are shown in Table 3.

[0059] Table 2

[0060]

[0061] Table 3

[0062]

[0063] First, static glassware corrosion was carried out, using an engine coolant corrosion tester, according to the standard test method of national standard SH / T0085, and the test lasted for 336 hours at 80°C. The quality changes of the metal test pieces before and after the test are shown in Table 4. It can be seen from the figure that after a long period of corrosion test, the corrosion resistance of Example 1 is the best. Comparison of surface changes of metal test pieces before and after the test Figure 1 As shown, it can also be seen in the figure that there is almost no trace of corrosion on the surface.

[0064] Table 4

[0065]

[0066]

[0067] And according to the test results, the weight changes of each material in Example 1 in Table 4 are all within the allowable range of the national standard. Among them, the weight changes of copper, brass, and steel are relatively small, indicating that the coolant has low corrosiveness to these metals. The weight changes of cast aluminum and aluminum materials also meet the standards, indicating that the coolant can effectively protect these aluminum materials. In general, Example 1 performs well in the static glassware corrosion test, has low corrosiveness, can meet the requirements of electric vehicle-specific coolant, and provides a guarantee for the stable operation of the electric vehicle cooling system.

[0068] At the same time, the coolant in Example 1 was subjected to a hot surface corrosion test using an engine coolant cast aluminum corrosion tester. According to the standard test method of national standard SH / T 0620, the test was continued at 135°C for 168 hours. The test results are shown in Table 5. The cast aluminum test blocks before and after the test are compared. Figure 2 As shown. Figure 2 It can be seen that the cast aluminum test block has obvious changes in appearance before and after the test. The surface of the test block is relatively smooth before the test, but there are certain signs of corrosion after the test. However, the specific degree of corrosion is analyzed in combination with the data in Table 3. Example 1 has a certain impact on the cast aluminum test block in the hot surface corrosion test, but it meets the national standard requirements and can meet the use needs of electric vehicles.

[0069] Table 5

[0070] <![CDATA[Mass change / (mg / cm 2 )]]> ±1.0 -1 The amount of solution precipitation after the test / mL ≤0.05 <0.5

[0071] Finally, a cyclic bench corrosion test was conducted on Example 1. A corrosion detector was used to simulate the use of pure electric vehicle coolant. According to the standard test method in Appendix C of GB / T29743.2, the test was continued at 80°C for 1064 hours. The surface changes of the metal test pieces before and after the test were compared. Figure 3 As shown, the weight change of the metal test piece before and after the test is shown in Table 6. According to the results of the cyclic bench corrosion test, the weight changes of each material in Example 1 meet the requirements of the national standard. The corrosion degree of copper, brass, steel and various aluminum materials is relatively low, indicating that the coolant has a good protective effect on these metals. In addition, the pH value of the solution after the test is 8, the change value is within a reasonable range, and the conductivity at 25°C is 59μs / cm, which is lower than the national standard limit. Overall, the coolant performed well in the cyclic bench corrosion test and can meet the use needs of electric vehicles.

[0072] Table 6

[0073]

[0074] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A low-conductivity coolant for electric vehicles, characterized in that: The low-conductivity electric vehicle-specific coolant comprises ethylene glycol, sodium nitrate, octanoic acid, butyl phosphate, benzotriazole, polyether-modified silicone defoamer, triethanolamine, imidazole, pigment blue, and limonin; Among them, calculated by mass fraction, ethylene glycol is 95-100%, sodium nitrate is 0-0.05%, caprylic acid is 0.2-0.4%, butyl phosphate is 0-0.01%, benzotriazole is 0.1-0.4%, polyether modified silicone defoamer is 0.05-0.1%, triethanolamine is 0.5-2%, imidazole is 0-0.3%, pigment blue is 0.02-0.06%, and limonin is 0.05-0.1%.

2. The low-conductivity cooling liquid for electric vehicles according to claim 1, characterized in that: The low-conductivity electric vehicle-specific coolant comprises, by mass fraction, 98.352% of ethylene glycol, 0.03% of sodium nitrate, 0.3% of octanoic acid, 0.008% of butyl phosphate, 0.12% of benzotriazole, 0.08% of polyether-modified silicone defoamer, 1% of triethanolamine, 0.04% of pigment blue, and 0.07% of limonin.

3. A method for preparing a low-conductivity cooling liquid for electric vehicles, characterized in that: include, The ingredients are prepared according to the mass percentages of any one of claims 1 to 2, ethylene glycol, sodium nitrate, and deionized water are added to the reactor in sequence, and stirred sufficiently to mix them evenly; then caprylic acid and butyl phosphate are added and stirred continuously until they are evenly mixed; finally, benzotriazole and defoaming agent are added and stirred evenly until no turbidity exists; then triethanolamine and imidazole are added to the reactor, stirred to make them evenly distributed, and finally pigment blue and bittering agent are added and stirred until they are evenly mixed; The mixture is filtered using filter cloth to obtain the low-conductivity special coolant for electric vehicles.

4. The preparation method according to claim 3, characterized in that: The ethylene glycol, sodium nitrate and deionized water are added into the reaction kettle in sequence and stirred sufficiently to be mixed evenly, wherein the stirring time is 20 to 40 minutes.

5. The preparation method according to claim 3, characterized in that: The stirring time of adding octanoic acid and butyl phosphate and continuing stirring until uniform mixing is 20 to 40 minutes.

6. The preparation method according to claim 3, characterized in that: The stirring time of adding triethanolamine and imidazole into the reaction kettle is 30 to 50 minutes.

7. The preparation method according to claim 3, characterized in that: The stirring time for adding the pigment blue and the bittering agent until they are evenly mixed is 5 to 10 minutes.

8. The preparation method according to claim 3, characterized in that: The stirring time for adding benzotriazole and defoaming agent is 30 to 50 minutes.

9. The preparation method according to claim 3, characterized in that: The conductivity of the ultrapure water solution used in the reactor is lower than 0.3 μs / cm.

10. Use of the low-conductivity cooling liquid for electric vehicles as claimed in claims 1 to 2 in electric vehicles.

Citation Information

Patent Citations

  • Anhydrous coolant and preparation method thereof

    CN105524598A

  • A fuel cell cooling liquid and application thereof

    CN109148915A

  • Heat transfer fluids and methods for preventing corrosion in heat transfer systems

    CN109790447A

  • Antirust cooling liquid as well as preparation method and application thereof

    CN116333694A

  • Hydrogen fuel cell cooling liquid corrosion inhibition complexing agent as well as preparation method and application thereof

    CN116463632A

Cited By

  • High-stability organic cooling liquid and preparation method thereof

    CN120290151A